Hierarchical porous carbon foam electrodes fabricated from waste polyurethane elastomer template for electric double-layer capacitors - Mahitha Udayakumar; Pál Tóth; Henrik Wiinikka; Jaskaran Singh Malhotra; Blaz Likozar; Saso Gyergyek; Anett Katalin Leskó; Ravikumar Thangaraj; Zoltán Németh (Scientific Reports, 2022)
Abstract Plastic waste has become a major global environmental concern. The utilization of solid waste-derived porous carbon for energy storage has received widespread attention in recent times. Herein, we report the comparison of electrochemical performance of porous carbon foams (CFs) produced from waste polyurethane (PU) elastomer templates via two different activation pathways. Electric double-layer capacitors (EDLCs) fabricated from the carbon foam exhibited a gravimetric capacitance of 74.4 F/g at 0.1 A/g. High packing density due to the presence of carbon spheres in the hierarchical structure offered excellent volumetric capacitance of 134.7 F/cm3 at 0.1 A/g. Besides, the CF-based EDLCs exhibited Coulombic efficiency close to 100% and showed stable cyclic performance for 5000 charge–discharge cycles with good capacitance retention of 97.7% at 3 A/g. Low equivalent series resistance (1.05 Ω) and charge transfer resistance (0.23 Ω) due to the extensive presence of hydroxyl functional groups contributed to attaining high power (48.89 kW/kg). Based on the preferred properties such as high specific surface area, hierarchical pore structure, surface functionalities, low metallic impurities, high conductivity and desirable capacitive behaviour, the CF prepared from waste PU elastomers have shown potential to be adopted as electrodes in EDLCs.